Coronary Sinus Morphology in Patients with Posteroseptal Atrioventricular Accessory Pathways - Sou Takenaka, MD; Yukiko Nakano, MD; Hidekazu Hirao, MD; Hiroki Teragawa, MD; Tetsuji Shingu, MD; Kazuaki Chayama, MD (Journal of Arrhythmia, 2006)
Background: There have been numerous reports about coronary sinus (CS) anomalies related to posteroseptal accessory pathways (APs). The purpose of this study was to explore the diameter and morphology of CS in patients with posteroseptal APs. Methods: We performed direct CS angiography in 105 patients with 22 posteroseptal APs and 83 APs in other regions, and 25 control subjects. We compared the diameter of the CS ostium in all subjects, and assessed the correlation of the local activation time in the patients with posteroseptal APs. Results: The proximal size (diameter) of the CS in the patients with posteroseptal APs (13:6 ± 1:1 mm) was larger than that in the patients with other types of APs (10:2 ± 1:8 mm [p < 0:001]) and that in the control subjects (9:6 ± 1:5 mm [p < 0:001]). Dilatation of the CS in the patients with posteroseptal APs extended up to 20 mm inside the CS. In 15 (68%) of the patients with posteroseptal APs, the proximal site of the CS demonstrated a windsock appearance. Conclusions: We concluded that the larger size and the wind cone appearance of proximal CS were unique structural characteristics in most patients with posteroseptal APs.